If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
(-1/2)*(6*x-(1/3)) = 0
(-1/2)*(6*x-1/3) = 0
-1/2*(6*x-1/3) = 0
( -1/2 )
-1/2 = 0
x belongs to the empty set
( 6*x-1/3 )
6*x-1/3 = 0 // + 1/3
6*x = 1/3 // : 6
x = 1/3/6
x = 1/18
x = 1/18
| 5p^2=230 | | 9x-8=x+10 | | 5x^2+4x-48=0 | | -2=-3/5x-3 | | 5(x)=20*1.03x | | -6b+2b-5b-3b+4b=-8b | | 40n^2+36n-28=0 | | 3x+20=2x+20-2r-40 | | 24+7=-4-9 | | -6b+2b-5b-3b+4b=18b | | y-5=0.11(x+9) | | 3n+7=82 | | 16=10-(4x+2) | | 5.34086e=231 | | -16t^2+80t+4=h(t) | | 4x=12+3x-x | | 1/2(6x-1/3) | | 72=-8m-24 | | 3x-43=2x-13 | | y-7=8(x-6) | | 3(x+5)=ex | | 2x+1=1-3x | | y+9=-5(x+6) | | 12x^2-26=x | | 72=-84-24 | | 0.3x^2-x=0 | | 7x-9*3=5x-6 | | y+10=7(x-9) | | -8+49r^2=-4 | | 8y-12=4y+8 | | y=85+10x | | -7=1-2b-2b |